Influence of Demographic Factors on Satisfactory Usse of Electronic Libraries in Northern Nigeria - S.A.Sadiku, A.O.Issa, A.O.Idown,A.L.Folorunsho (IJoLIS, 2024)
Purpose: The advent of ICT has come to change the role of libraries in terms of provision of information recourses andn services.